Community Empowerment in The Prevention of Stunting for Children Under Five : by Optimizing the Role of Cadres, Health Education and Family Assistance - Siregar, Fazidah Aguslina; Surdayati, Etti; Nurmaini (Talenta Publisher, 2020)
Stunting is a health problem needs serious attention. In Bagan Deli Village, the proportion of children who are stunted was 10.37% and children with poor nutritional status was 2.9%. It has an impact on growth disorders, immune system, and furthermore, impaired children's intelligence. Optimizing the role of cadres and family involvement in stunting prevention is necessary. The aims of this activity was to educate cadres and parents in monitoring the growth of children under five, nutritional intake of children and implement of nutritional intake in daily life. From this activity, it can be seen that the cadres' knowledge increases in monitoring the growth and nutrition of children under five after training. From the health status examining on children, it was found that 33.3% of children under five were malnourished, 33.3% were with poor nutrition and 33.3% were with good nutrition. Education and family assistance are provided to parents in preparing a balanced healthy menu for children. It was suggested that parents prepared daily healthy menu and monitoring the nutrition of children under five. Therefore, community empowerment in preventing stunting in children under five is necessary